METODE PEMBELAJARAN DENGAN PENDEKATAN DISCOVERY LEARNINGDALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KREATIF - Muhammad Munir; Hijriati Sholehah (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2019)
The learning process is inspiring, fun, challenging, and motivates students to participate actively, providing space for students to be creative according to their abilities. Therefore we need a learning method with an appropriate approach in order to explore student abilities in aspects of skills. Learning with discovery learning approach is one approach that can be applied to develop students' skills, namely the ability to think creatively. Learning by discovery emphasizes the activities of students to learn on their own and eventually will find results. Here the teacher is no longer a giver of knowledge but acts as a facilitator or supervisor. That is because the discovery learning approach provides opportunities for students to explore thinking skills in finding their own knowledge and building creative reasoning according to their respective abilities. Indirectly students will be directed to become a researcher who is required to have the ability to think creatively.